The State Secrets Privilege and the War on Terror: An Annotated Bibliography. Issue 1 (2nd January 2017) - Venie, Todd
ABSTRACT: This selective annotated bibliography is a guide to scholarly articles about use of the State Secrets Privilege during the War on Terror. Use of the privilege became controversial during the presidential administration of George W. Bush, resulting in a scholarly debate over the privilege and the propriety of its use in litigation concerning measures taken by the United States government in the years following the terrorist attacks of 11 September 2001. This bibliography is intended to provide an overview of the scholarly literature to lawyers, scholars, and students.